(untitled) (Universal International Scientific Journal, 2026)
This thesis provides a comprehensive analysis of the impact of pedagogical communication on the emotional intelligence and intellectual development of students. In the modern education system, communication between teacher and student is considered not only a means of imparting knowledge, but also an important factor in personal development.